This I Believe - Epstein, Benjamin R. (Tufts Archival Research Center, 2006)
Benjamin Epstein, National director of the Anti-Defamation League, describes the faith in people he had as a child and how he lost it after studying abroad in Nazi Germany and how he again regained it after his return to the United States.